Assistance enhances the motivation of teachers and students through the introduction of multimedia-based learning at SMP Negeri 12 Torgamba - Vinny Tryandini; Pristiyono; Nasution, Meisa Fitri (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
In creating engaging learning experiences, educators need skills in using digital media in teaching. One effort that can be implemented to address the conditions present in the school environment during this era of advancing digital technology, and to attract students' interest in learning, is designing and developing multimedia-based instructional media. To achieve this objective, it is necessary to conduct training and provide assistance to educators. This training is conducted by introducing and offering tutorials on the use of Microsoft Office software and educational film screenings. The results of this community service include improved understanding among educators regarding the development of multimedia-based instructional media, enhanced ability to apply software in creating learning materials through discussions and Q&A sessions, and increased student interest in the teaching and learning process at school.